Pemantauan dan Upaya Peningkatan Intensitas Pencahayaan Lokal Pada Pekerjaan Menjahit di KUB Mampu Jaya untuk Mencegah Kelelahan pada Mata - Sahri, Moch; Ayu, Friska; Sunaryo, Merry; Zakkiy Fasya, Abdul Hakim; Faradis, Hani; Wicaksono, Rizky Rahadian (Al-Qalam Institute, 2022)
The purpose of this community service activity is to helpincrease the intensity of additional lighting in each work unitthat is still low in lighting intensity. The implementationmethod in this activity starts from a site survey, coordinationwith related parties such as the Surabaya city health officeand the local health center as the coordinator of theoccupational health post. Then measure the intensity oflighting and increase additional lighting on work units withless lighting intensity. The measurement results in all workunits obtained an average lighting intensity value of 107 lux(standard 500 lux). After installing additional local lighting,the results obtained are the intensity of the lighting with anaverage of 928 lux. When viewed from the measurementresults before and after local lighting was installed, there wasan increase in lighting intensity. After the intervention withthe installation of local lighting there was an increase in theintensity of the lighting in accordance with the standardlighting for the type of sewing work. This condition needs tobe maintained so that workers feel comfortable andcomplaints of eye fatigue can be minimized. In addition, it isnecessary to measure periodically to ensure the intensity ofthe lighting is in accordance with the standard.